Analyzing Position, Velocity and Acceleration Graphs using Arduino (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
Motion graphics and their relationships within the scope of the kinematics unit are difficult topics for students to learn. In this study, an Arduino-based in-class physics activity was developed, in which students can analyze position-time, velocity-time and acceleration-time graphs practically. Within the scope of the study, Arduino UNO and HC-SR04 distance sensors, which are very low cost and easily obtainable, were used in the material development process. Data analyzes were also carried out using the Excel program. The position values and time values of a simple car moving with constant acceleration were collected with the help of Arduino and then these data were transferred to the Excel program. Instant velocity and acceleration values were determined on the Excel platform. Then, graph types and relationships between graphs were analyzed by drawing time-dependent graphs of position, velocity and acceleration with the help of Excel program. The motion acceleration was determined as 2.388 m/s2 both by taking the second derivative of the position-time equation with respect to time and by using the slope of the time-dependent graph of the instantaneous velocity values found. Furthermore, the displacement was calculated as 0.363 m using first and last position values that were directly read from the distance sensor and 0.348 m using the area under the velocity-time graph. The two values are very close to each other, with a difference of +4.1. The change in velocity was calculated as 0.845 m/s by taking the difference of the initial and final velocity and calculating the area under the acceleration-time graph. In addition to providing students with important educational gains in graphic subjects, it is expected that such a study carried out with students in the classroom will also be effective in the development of technological literacy and data analysis skills.